A taxonomic revision of the genus Sirthenea (Hemiptera: Heteroptera: Reduviidae) of the Old World - Chłond, Dominik (Zootaxa, 2018)
This paper presents a taxonomic revision of 28 described species of the genus Sirthenea Spinola, 1837 (Hemiptera: Heteroptera: Reduviidae: Peiratinae) distributed in the Afrotropical, Oriental, Palearctic, Oceanian and Australian zoogeographical regions. The following new synonymies are proposed: Sirthenea africana Distant, 1903 = S. rapax Horváth, 1909, syn. nov. = S. leonina Horváth, 1909, syn. nov. = S. bequaerti Schouteden, 1913, syn. nov. = S. leontovitchi Schouteden, 1931, syn. nov.; Sirthenea picescens Reuter, 1887 = S. atrocyanea Horváth, 1909, syn. nov.; S. rodhaini Schouteden, 1913 = S. collarti Schouteden, 1931, syn. nov. = S. angolana Villiers, 1958, syn. nov.; S. flavipes (Stål, 1855) = S. clavata Miller, 1948, syn. nov. = S. bharati Sucheta & Chopra, 1988, syn. nov. = S. koreana Kerzhner & Lee, 1996 syn. nov. = S. melanota Cai & Lu, 1990, syn. nov. = S. nigripes Murugan & Livingstone, 1990, syn. nov.; S. obscura (Stål, 1866) = S. glabra (Walker, 1873), syn. nov. A neotype is designated for S. picescens Reuter, 1887. Three species, S. erythromelas (Walker 1873), S. fulvipennis (Walker, 1873) and S. sobria (Walker, 1873), are excluded from the genus Sirthenea. Two new species from the Oriental Region, S. kali sp. nov. (India) and S. setosa sp. nov. (Malaysia) are described. Identification keys are provided for the subgenera and species from each zoogeographical region treated. Drawings of dorsal habitus and genitalic structures, drawings and images of selected morphological characters, and distribution maps of all valid species are presented.